2021
DOI: 10.1039/d1ra06253k
|View full text |Cite
|
Sign up to set email alerts
|

Improving the catalytic performance of Pichia pastoris whole-cell biocatalysts by fermentation process

Abstract: Fermentation process was applied to relieve the substrate transport-limitation of P. pastoris whole-cell biocatalysts, which was much simpler, more energy-saving and greener than c traditional permeabilizing reagent and ultrasonication treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…By overexpressing the transcription factor Yap1p to downregulate ROS level, twofold enhanced secretion of trypsinogen was achieved in P. pastoris (Delic et al 2014). It has been reported that overexpression of the HAC1 gene leads to a reduced ROS level in yeast, which is consistent with our results (Wang et al 2021). We also discovered a significant decrease in rhPH-20 secretion after supplementing H 2 O 2, ROS precursor, which might indicate ScHac1p overexpression exerts a protective effect on rhPH-20 secretion by reducing ROS level.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By overexpressing the transcription factor Yap1p to downregulate ROS level, twofold enhanced secretion of trypsinogen was achieved in P. pastoris (Delic et al 2014). It has been reported that overexpression of the HAC1 gene leads to a reduced ROS level in yeast, which is consistent with our results (Wang et al 2021). We also discovered a significant decrease in rhPH-20 secretion after supplementing H 2 O 2, ROS precursor, which might indicate ScHac1p overexpression exerts a protective effect on rhPH-20 secretion by reducing ROS level.…”
Section: Discussionsupporting
confidence: 92%
“…We also discovered a significant decrease in rhPH-20 secretion after supplementing H 2 O 2, ROS precursor, which might indicate ScHac1p overexpression exerts a protective effect on rhPH-20 secretion by reducing ROS level. However, while several studies have also shown that Hac1p overexpression can reduce ROS levels and relieve oxidative stress in P. pastoris (Graf et al 2008;Wang et al 2021), how the ROS level was downregulated by Hac1p overexpression is still unclear. Therefore, future investigations are needed to explore the exact mechanism of ROS reduction in Hac1p-overexpressing yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…Methanol concentration was determined by high performance liquid chromatography [ 16 ]. A 1 mL sample from the fermentation was centrifuged at 6000 rpm for 5 min and the supernatant was filtered through a 0.2 μm filter using a syringe and analyzed on an LC-16 high performance liquid chromatograph (Shimadzu) equipped with a differential refractive index detector (RID-20 A) using a Carbomix H-NP10: 8% column (Sepax Technologies, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The tubes containing centrifuged cells were dried at 105 • C to a constant weight to determine the DCW. The relationship between the OD 600 and DCW was represented via empirical Equation (1), OD 600 L −1 = 0.24 g DCW L −1 [54]. The nitrogen content of the homogenized residues was analyzed using the Kjeldahl method [55].…”
Section: Biomass and Crude Protein Analysismentioning
confidence: 99%